No Compassion for Muslims?: how Journalistic News Coverage of Terrorist Crimes Influences Emotional Reactions and Policy Support Depending on the Victim’s Religion - Schmuck, Desirée (Crime & delinquency, 2023)
Islamist terrorist attacks have become a salient threat to Western countries, and news coverage about such crimes is a key predictor of public emotional reactions and policy support. We examine the effects of two key characteristics of terrorism news coverage: (1) the victim’s religion and (2) first-person narratives that facilitate perspective taking. A quota-based experiment (N = 354) revealed that irrespective of the narrative type, news reports that mention the victims’ Muslim religion induce less anger and compassion, but more joy among non-Muslim news consumers. However, fear was equally induced by all news articles. As a consequence, fear, anger, and joy predicted support for more restrictive terrorism policies, while anger and compassion were related to more support for victim compensation.